Morphotectonic Identification of the Active Ransiki Fault Zone as a Source of Shallow Seismicity in South Manokwari, West Papua: Integrating Stream Length–Gradient Index and Lineament Analysis - Tandirerung, Restu; Alzair, Nur (Journal of Geoscience, Engineering, Environment, and Technology, 2026)
The Ransiki area, which is in South Manokwari, West Papua, lies in a tectonically active transition zone related to the oblique convergence between the Indo-Australian and Pacific plates. Although shallow seismic activity has already been detected, the geometry and seismo-tectonic behavior of local fault structures have not been characterized yet. This work aims to explore the morphotectonic framework of the region by combining quantitative geomorphic indices and structural evidence. From 8–30 m resolution DEMNAS data multi-azimuth lineaments were extracted and Stream Length–Gradient Index (SLI) was derived on 42 river segments. The distribution of lineament density and SLI anomalies were correlated using Pearson coefficient and verified with field observation of fault scarps, triangular facets and slickensides. The results show relevant NNW–SSE lineaments (N330°-N340°E) having high local SLI values (>500) that are more concentrated in the eastern sector of Ransiki. Field evidences evidence envisage an active sinistral strike-slip deformation along this trend. These combined geomorphic- and structural-based indicators attest the actively deforming character of the Ransiki Fault Zone as a transpressional shear corridor that transfers deformation between the Sorong Fault System and the Arfak upliftement. The methodology applied in this case study offers an efficient tool to identify active faults in tropical regions with sparse geophysical ground data and provides valuable input for seismic hazard assessment in eastern Indonesia.